ГОТОВНІСТЬ МАЙБУТНЬОГО ПЕДАГОГА ДО РЕАЛІЗАЦІЇ ПРИНЦИПУ ОСОБИСТІСНОГО ПІДХОДУ В ОСВІТІ: ТЕОРЕТИЧНИЙ АСПЕКТ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
In this article author touches the problem of necessity of training the future teacher to the realization of the personal approach principle in educational process, touching theoretical aspects of declaration of essence of personally oriented approach in education and concept of readiness of the future teacher to this activity.